Pengaruh Kemajuan Teknologi Berbasis Aplikasi Digital terhadap Kualitas dengan Efektivitas Kerja Pegawai sebagai Variabel Intervening pada PT. PLN (PERSERO) Unit Induk Wilayah Sulselbar - Syamsuryani, Syamsuryani; Abdullah, Wahidah; Jafar, Ahmad (Study of Scientific and Behavioral Management, 2024)
ABSTRACT This study aims to determine the effect of advances in digital application-based technology on work quality through employee work effectiveness at PT. PLN (Persero) Sulselrabar Main Unit. In the research, the variables used are advances in technology based on digital applications as the independent variable, work quality as the dependent variable and work effectiveness as the intervening variable.The type of research used is quantitative research with an associative approach. Data collection techniques in this study used questionnaires and documentation, with a total sample of 135 respondents.. In this study using SPSS 26 software as a data analysis technique. The results showed that advances in digital application-based technology had a positive and significant effect on work effectiveness, advances in digital application-based technology had a positive and significant effect on work effectiveness, work effectiveness had a positive and significant effect on work quality, and advances in digital application-based technology had a positive and significant effect on work quality through employee work effectiveness Keywords: Advances in Digital Application-Based Technology, Quality of Work, Work Effectiveness.